Pembangunan Rumah Susun Sebagai Solusi Strategis Untuk Mengatasi Keterbatasan Lahan Di Kota Bengkulu - Noera Safira; Vingky Bintang Fernando; Renita Kusuma Dewi; Febriyanti Hasibuan; M Yamani (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The density of urban settlements has resulted in the loss of agricultural land and green open space as a result of population growth, especially in the Bengkulu City area, which is always experiencing an increase. The high demand for new houses has the impact of causing urban spaces to become increasingly congested and creating slum residential areas. The area of ​​urban land with an unequal number of residents results in a decline in environmental quality and a decline in the level of welfare of residents in Bengkulu City. Therefore, it is necessary to build public housing which can create integrated and environmentally friendly residential areas in order to increase the effectiveness and efficiency of space and land utilization so that it is more optimal. Therefore, flats are a solution to streamline residential development in Bengkulu City.